A Trend Model for Alzheimer's Mortality - Örjan Hallberg (International Association of Physical Chemists (IAPC), 2015)
In Sweden, mortality rates from Alzheimer's disease have increased since early 90's.  In this study, we compared rates reported from 2006-2012 with projected trends determined previously and found a good fit.  The objective of this study was to investigate if increased mortality can be modeled as a single exponential function of time lived in a new environment, where the risk of dying from Alzheimer's disease has been increased.  The results demonstrated that the exponential model can be used to predict future mortalities for different scenarios, and that it can also project age-specific trends.  We conclude that increasing mortality rates from Alzheimer's disease seem caused by an environmental change introduced since the 1990's.  Since similar trend breaks also have been reported for different cancers, responsible authorities should seriously address this problem to pinpoint causative factors.